Aproximación al valor de Cemex Colombia S.A. : por medio de diferentes métodos de valoración (2017)
"The project makes an approximation to the value of CEMEX Colombia S.A. By relative valuation and discounted cash flow. Likewise, a macroeconomic analysis of the sector in which CEMEX Colombia carries out its operations is made and the financial status of the company is analyzed. The above, to understand the state of the company and its performance over time. Statistical tools were used to facilitate the projection of Financial Statements and the other finance tools. Thus, it was possible to carry out a financial analysis of the company and finally approach its value".-- Tomado del Formato de Documento de Grado.